Effect of phosphorus application on the performance of four cowpea varieties and two maize varieties under strip intercropping in Limpopo Province - Nkuna, Mzamani Knowledge (My University, 2019)
Limpopo Province is a semi-arid region prone to drought. Crop yields continue to decline due to low soil fertility and poor cropping systems. Cowpea is nutritionally rich in proteins essential for human consumption and livestock feeding. It fixes N2 which becomes available for the succeeding crop in rotation. For this reason, it is used as a companion crop in cereal-legume intercropping systems. Maize is one of the most important grain crops in South Africa, it serves as the major staple food for many households. Phosphorus is one of the macro-nutrient elements required by crops to produce satisfactory yields. The interactions between different rates of P fertilisation and cowpea-maize strip intercropping have not been studied in detail under rain-fed maize-cowpea strip intercropping in Limpopo Province. Many smallholder farmers in Limpopo Province obtain low yields due to the practice of mixed intercropping. Two season (2014/15 and 2015/16) experiments were laid out in a split-split plot design at Syferkuil farm to determine the performance of cowpea and maize varieties in cowpeamaize strip intercropping at varying P application rates. Treatments consisted of factors namely, P levels (0, 15, 30, 45 kg/ha), cropping system (monocropping and intercropping), maize varieties (WE3127 and ZM1423) and cowpea varieties (PAN311, TVu13464, IT86D-1010 and IT82D-889). Data were collected from growth and yield parameters that included (number of days to flowering, plant height, number of days to physiological maturity, root weight, number of pods per plant, unshelled net pod weight, number of cobs per plant, unshelled net cob weight and grain yield) in order to determine their performance. Results obtained revealed that P application levels significantly influenced most of the measured growth and yield parameters of both crops. PAN311 flowered earliest (49 days) across P levels. Increasing P application hastened the maturity of the varieties of PAN 311 and TVu13464 in both seasons. The P levels of 30 and 45 kg/ha reduced the number of days to maturity as compared to 0 and 15 kg/ha. TVu13464 variety produced more pods per plant (30) than other varieties. PAN311 yielded more grains (2491 kg/ha) than other varieties. Maize varieties performed well between P applications of 30 and 45 kg/ha. WE3127 yielded 3462 kg/ha whereas ZM1423 yielded 3306 kg/ha. Intercropping vi system performed better than monocropping system based on the measured growth and yield parameters. Two promising cowpea varieties (PAN311 and TVu13464) performed well and were selected based on their early maturity, drought tolerance and high yielding. Increasing P application levels increased crop yield. Optimum P levels for cowpea-maize strip intercropping were between 30 and 45 kg/ha. The calculated LER values were greater than one which indicates that intercropping was advantageous in land utilisation. The study showed the importance of P application in improving cowpea yield in cowpeamaize strip intercropping.
Thesis (M.Sc. Agriculture (Agronomy)) -- University of Limpopo, 2019
Keywords: Growing season; Cropping system; Phosphorus; Cowpea; Maize; Grain yield; Intercropping -- South Africa -- Limpopo; Cowpea -- South Africa -- Limpopo; Corn -- South Africa -- Limpopo; Phosphorus in agriculture